OS DESAFIOS DO PROCESSO DE ABORTO LEGAL: UMA REVISÃO INTEGRATIVA - Juscilene da Silva Maciel (2025)
Legal abortion is considered a serious public health problem in several developing countries, including Brazil, due to the obstacles faced in accessing this right. Discussions on this topic arise around legal, moral, religious, social and cultural aspects. The concept of abortion refers to the deprivation of birth, voluntary interruption of pregnancy, with the death of the product of conception, which occurs between 20 and 22 weeks or fetal weight of up to 500g. It can occur safely or unsafely. The Brazilian penal code in force since 1940 includes the decriminalization of abortion in patients who are victims of rape and in cases of risk to the life of pregnant women. The inclusion of cases of anencephaly, which occurred in 2012, can also be described as a milestone. The SUS is the main provider of this type of health care, and even after all these years of legalizing abortion, there are still challenges to be explained, experienced by both users and the multidisciplinary team in the environments in which they work. In view of the above, the following guiding question emerges. What are the challenges faced by users and multidisciplinary teams in legal abortion processes? This is an integrative review that will evaluate publications in journals in the areas of Health, Nursing, Law and Interdisciplinary from 2014 to 2024. Using the controlled descriptors: Legal Abortion, Sexual Violence and Health. The evaluation of the studies was carried out carefully so that they responded to the listed problems. It was evident that SUS users face access barriers, for example, such as the unequal distribution of accredited services across the country, lack of supplies, lack of information, shortage of qualified professionals who accept to perform legal abortion and slow evolution in the issue of legislation and care protocols. Regarding the multidisciplinary team, issues related to religious, moral, ethical, social and cultural aspects that were decisive for conscientious objection stood out. The need for debates, ongoing education, and the creation and dissemination of protocols and laws that address legal abortion also impact this controversial scenario.